Correlation of early contrast-enhanced ultrasound parameters with postoperative graft function and at six months after kidney transplantation - Taut, Tina; Kurz, Felix; Schlemmer, Heinz-Peter; Meinzer, Clara; Mahler, Christoph; Speer, Claudius; Benning, Louise; Göth, Daniel; Nusshag, Christian; Sommerer, Claudia; Schaier, Matthias; Zeier, Martin; Morath, Christian; Kälble, Florian (Ultrasound International Open, 2024)
Purpose We analyzed which contrast-enhanced ultrasound (CEUS) parameters are associated with reduced kidney function in the early postoperative period and are prognostic for kidney function six months after transplantation.Materials and Methods This prospective observational study included 74 patients in whom quantitative CEUS analysis and Doppler ultrasound were performed early after kidney transplantation (10±6 days). For each region of interest (ROI) the time-to-peak intensity (TTP) and the respective delta between ROIs within interlobar artery, cortex, and medulla were compared. Results were correlated with kidney function at the time of imaging and six months later.Results Patients with an eGFR<30 ml/min at the time of investigation had significantly slower cortical enhancement with a longer cortical TTP (cTTP: 16.1±0.9 vs. 11.7±0.7 sec, p<0.001), as well as a significant delay between the arterial and cortical phases (c–a), as shown in longer ∆TTP (c–a): 8.2±0.9 vs. 4.2 ± 0.5 sec, p<0.001. There was a significant negative correlation between cTTP and eGFR with a correlation coefficient of −0.37 (p<0.001), as well as between ∆TTP (c–a) and eGFR with a correlation coefficient of −0.40 (p<0.001). Reduced kidney function after 6 months correlated significantly with the findings of the initial CEUS examination (p=0.005, correlation coefficient −0.39).Conclusion CEUS revealed significant differences in temporal enhancement dynamics in patients with reduced kidney function after transplantation. Quantitative CEUS might therefore be able to depict graft function regarding microvascular damage and be of prognostic value regarding long-term renal outcomes.
Keywords: kidney transplantation; microvascular damage; kidney function; contrast-enhanced ultrasound